Cuantificación de los niveles de metales pesados (pb, hg) en sedimentos en tres localidades del estero grande, de la zona costera de la provincia de El Oro 2014. - Ortega Toro, Diana Carolina (2015)
In this research the presence of heavy metals in sediments (Hg and Pb) was evaluated by atomic absorption spectrophotometry to analyze and quantify the total content of Hg and Pb, with spray flame for the determination of Pb, hydride generation and atomization in a cell with quartz Hg for determining sediment to different depths (10, 20,30 cm). The extraction of analytes was carried out following the methodology by acid digestion, which gave excellent results because of this, it was concluded that the sediments represent a risk to biota and the concentration of Hg in the sediments were very higher in all sampling points for the three locations del Estero Great, these results, along with Canadian quality standards (CEQG, 2001) and (probable effect concentration - PEL) American standard.